Evidence of tobacco from a Late Archaic smoking tube recovered from the Flint River site in southeastern North America. (October 2018) - Carmody, S.; Davis, J.; Tadi, S.; Sharp, J.S.; Hunt, R.K.; Russ, J.
Abstract: Tobacco use was widespread amongst the indigenous populations throughout North and South America prior to European contact; however, the geographical and temporal spread of the plant is poorly understood. Organic residue analysis is providing a new source of information on the diffusion of tobacco based on the presence of nicotine extracted from smoking pipes recovered from archaeological contexts. Using gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-high-resolution mass spectrometry (LC-HRMS) we identified nicotine in a Late Archaic (1685-1530 cal B.C) smoking pipe from the Flint River site in Northern Alabama. This evidence suggests the exploitation of tobacco spread into the southeastern North America nearly a millennium earlier than the current hypothesis on the rate of dispersion of tobacco in pre-Columbian North America. Highlights: The manuscript reports on the detection of nicotine in a Late Archaic smoking tube (FS74) recovered from the Flint River Archaeological site. The age of the artifact was established by radiocarbon dating of contemporaneous deer bone collagen which sets the age of the smoking tube at 1685-1530 BC. As nicotine is a biomarker for tobacco, this resets the arrival of tobacco in North America by at least a millennium earlier than previous studies would indicate.